A right to care? unpaid work in European employment law - Busby, Nicole (Oxford : Oxford University Press, 2011)
The reconciliation of unpaid care work and paid employment is among the most pressing and difficult problems currently facing employment law. Nicole Busby assesses the potential to situate a right to care within employment law, and for the recognition of carer status as a means of protecting against discrimination in employment.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Labor laws and legislation -- European Union countries; Voluntarism -- European Union countries; Caregivers -- European Union countries